Combination Therapy of Chemotherapy or Radiotherapy and the Neurokinin-1 Receptor Antagonist Aprepitant: A New Antitumor Strategy? - Robinson, Prema; Coveñas, Rafael; Muñoz, Miguel (Current Medicinal Chemistry, 2023)
Background: Although chemotherapy is predominantly used for cancer treatment, it can be ineffective and can induce serious side effects and lead to chemoresistance. It is essential to discover novel drugs that can enhance the antitumor activity and at the same time, counteract the severe side effects, of chemotherapy. The substance P (SP)/neurokinin-1 receptor (NK-1R) interaction system is known to play a key role in the pathogenesis of cancer. Studies with NK-1R antagonists (such as aprepitant) denote that the NK-1R is a potential target for the treatment of cancer. Aprepitant combined with major chemotherapeutic drugs has shown the potential to increase antitumor activity and decrease side effects. Objective: Since malignant tumor cancer cells overexpress the NK-1R, this combination therapy is a promising approach for the treatment of all kinds of cancer. Since aprepitant shows potential of being a broad-antitumor drug, the repurposing of this NK-1R antagonist as an antitumor agent is warranted. Studies pertaining to combination therapy of aprepitant/radiotherapy will also be outlined in this review. The aim of this review is to provide an update on combinational studies pertaining to chemotherapy/radiotherapy and NK-1R antagonist in cancer. Conclusion: This combination strategy once confirmed, might open the door to a new era in chemotherapy and radiotherapy with greater antitumor activity and fewer side effects. This treatment strategy could possibly translate into higher cure rates, better quality of life and fewer sequelae in cancer patients.
Keywords: Aprepitant